2016
DOI: 10.14429/djlit.37.1.10772
|View full text |Cite
|
Sign up to set email alerts
|

RFID Technology in Libraries: A Review of Literature of Indian Perspective

Abstract: Implementation of Radio Frequency IDentification technology in libraries in a developing country like India has brought remarkable improvements in the services such as shelf charging-discharging, automated handling of materials, security, high-speed inventory and moved beyond security to become tracking systems that combine security with more efficient tracking of materials throughout the library, reduced the data entry errors, enhanced customer service, and records updates. This article is an attempt to asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Indian Institutes of Technology are one of the autonomous public institutions in India, Indian Institute of Technology -Delhi has recently implemented the RFID technology in the library for the smooth operation of library resources. Gupta and Margam (2016) observed that this technology is used in many areas like issuing and returning of the books, as 68 percent believed that RFID system had increased the affordability of books by using smart cards through an issue and return kiosks. More research has to be conducted about the usage of this technology in many universities.…”
Section: Paperless Documentation By Implementation Radio Frequency Identification In Librariesmentioning
confidence: 99%
“…Indian Institutes of Technology are one of the autonomous public institutions in India, Indian Institute of Technology -Delhi has recently implemented the RFID technology in the library for the smooth operation of library resources. Gupta and Margam (2016) observed that this technology is used in many areas like issuing and returning of the books, as 68 percent believed that RFID system had increased the affordability of books by using smart cards through an issue and return kiosks. More research has to be conducted about the usage of this technology in many universities.…”
Section: Paperless Documentation By Implementation Radio Frequency Identification In Librariesmentioning
confidence: 99%
“…Librarians are generally regarded as early adopters of new service technologies (e.g. Singh and Mahajan, 2014; Gupta and Margam, 2017). Sometimes early adopters find that the technologies they chose may not become popular or may produce unexpected reactions from stakeholders.…”
Section: Introductionmentioning
confidence: 99%